On‐Surface Assembly of Hydrogen‐ and Halogen‐Bonded Supramolecular Graphyne‐Like Networks. Issue 24 (1st April 2020) - Yang, Zechao; Fromm, Lukas; Sander, Tim; Gebhardt, Julian; Schaub, Tobias A.; Görling, Andreas; Kivala, Milan; Maier, Sabine
Abstract: Demonstrated here is a supramolecular approach to fabricate highly ordered monolayered hydrogen‐ and halogen‐bonded graphyne‐like two‐dimensional (2D) materials from triethynyltriazine derivatives on Au(111) and Ag(111). The 2D networks are stabilized by N⋅⋅⋅H−C(sp) bonds and N⋅⋅⋅Br−C(sp) bonds to the triazine core. The structural properties and the binding energies of the supramolecular graphynes have been investigated by scanning tunneling microscopy in combination with density‐functional theory calculations. It is revealed that the N⋅⋅⋅Br−C(sp) bonds lead to significantly stronger bonded networks compared to the hydrogen‐bonded networks. A systematic analysis of the binding energies of triethynyltriazine and triethynylbenzene derivatives further demonstrates that the X3 ‐synthon, which is commonly observed for bromobenzene derivatives, is weaker than the X6 ‐synthon for our bromotriethynyl derivatives. Abstract : The on‐surface assembly of hydrogen‐ and halogen‐bonded supramolecular graphyne‐like networks from functionalized triethynyltriazine derivatives on metal surfaces, Au(111) and Ag(111), is described. The networks are stabilized by N⋅⋅⋅H−C(sp) bonds and N⋅⋅⋅Br−C(sp) bonds to the triazine core.